Accurasy of the qibla diraction of the astronomy perspective graveyard in Batulappa village patimpeng district bone regensy: Accurasy of the qibla diraction of the astronomy perspective graveyard in Batulappa village patimpeng district bone regensy - Basmin, Indasari; Alimuddin,; Abu Bakar, Syukur (HISABUNA: Jurnal Ilmu Falak, 2023)
Qibla direction is identical to the implementation of worship, both when they want to perform prayers and bury or bury the body. A person can be said to be facing the Qiblah if all his limbs are facing towards the Ka’bah which is the benchmark for Muslims in worship. The current case is that it turns out that in Batulappa Village, Patimpeng District, Bone Regency, grave diggers only follow the position of pre-existing graves and they rely on an approximate method by looking at the position of the sun setting from East to West, so that is the direction of Qibla and the position of the graves in the village. irregular. This is due to the lack of understanding of the people who know about determining the actual direction of the Qibla of the grave. Therefore, the researcher will go directly to the field to check the Qibla direction of the cemetery in Batulappa Village, Patimpeng District, Bone Regency by using a special stick, Qibla arc (as a tool) and manual calculations based on the latitude and longitude of an area. Based on the measurement method carried out by researchers in determining the Qibla direction directly in the field using tools such as the istiwa' stick, the Qibla arc and the Qibla direction reckoning method at the three burial places, namely the Kallecce Grave, Bulu Kacce Grave, and the Bilalalng Bulu Grave. The results found by researchers at three locations at the cemetery were that in the Kallecce grave a deviation of 2º-22º was found, in the Bulu Kacce grave a deviation of 3º-7º, while the deviation was found in the Bulu Bilalang grave 7º-11º.